2010
DOI: 10.1523/jneurosci.1113-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Is My Mobile Ringing? Evidence for Rapid Processing of a Personally Significant Sound in Humans

Abstract: Anecdotal reports and also empirical observations suggest a preferential processing of personally significant sounds. The utterance of one's own name, the ringing of one's own telephone, or the like appear to be especially effective for capturing attention. However, there is a lack of knowledge about the time course and functional neuroanatomy of the voluntary and the involuntary detection of personally significant sounds. To address this issue, we applied an active and a passive listening paradigm, in which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 33 publications
(36 reference statements)
5
28
0
Order By: Relevance
“…phase-locked) cortical GBRs reflect initial stages of sensory perception (Joliot et al, 1994; Singer, 1999). Relationships between gamma oscillations and other cognitive processes have been reported, including selective attention (Fries et al, 2001; Tiitinen et al, 1993), stimulus salience (Roye et al, 2010), associative and perceptual learning (Miltner et al, 1999), sensorimotor integration (Murthy and Fetz, 1992), and object representation (Tallon-Baudry and Bertrand, 1999). Such findings, observed across human and animal studies, demonstrate a phylogenetically conserved role for gamma synchrony in coordinating distinct aspects of sensory information among distributed brain regions.…”
Section: 0 Gamma Oscillations: Neurophysiology Cognitive Correlatesmentioning
confidence: 99%
“…phase-locked) cortical GBRs reflect initial stages of sensory perception (Joliot et al, 1994; Singer, 1999). Relationships between gamma oscillations and other cognitive processes have been reported, including selective attention (Fries et al, 2001; Tiitinen et al, 1993), stimulus salience (Roye et al, 2010), associative and perceptual learning (Miltner et al, 1999), sensorimotor integration (Murthy and Fetz, 1992), and object representation (Tallon-Baudry and Bertrand, 1999). Such findings, observed across human and animal studies, demonstrate a phylogenetically conserved role for gamma synchrony in coordinating distinct aspects of sensory information among distributed brain regions.…”
Section: 0 Gamma Oscillations: Neurophysiology Cognitive Correlatesmentioning
confidence: 99%
“…We wanted to test experimentally whether participants would be more disrupted by their own cell phone's ringtones than by someone else's ringtone. There is evidence from event-related potential studies that the brain's response to the own ringtone differs from the response to another ringtone [17,18] leaving open the opportunity that one's own ringtone has a higher disruptive potential on cognitive performance compared to that from another person, but it may also be the case that although the brain signals differ between these ringtone types, overt task performance does not.…”
Section: Introductionmentioning
confidence: 99%
“…Cortical oscillatory activity in the gamma-band frequency range is supposed to reflect the activation of distributed cortical stimulus representations (Fries, 2005;Engel & Singer, 2001). This activation can be influenced by the existence of stimulusspecific memory representations (Roye, Schröger, Jacobsen, & Gruber, 2010;Herrmann, Lenz, Junge, Busch, & Maess, 2004;Herrmann, Munk, & Engel, 2004). For example, the study by Herrmann, Lenz, et al (2004) demonstrated that real-world objects, which are represented in long-term memory, evoked a stronger eGBR at occipital electrodes than nonsense objects without a long-term memory representation.…”
Section: Introductionmentioning
confidence: 99%